Developing keratin sponges with tunable morphologies and controlled antioxidant properties induced by doping with polydopamine (PDA) nanoparticles. (15th November 2016) - Posati, T.; Sotgiu, G.; Varchi, G.; Ferroni, C.; Zamboni, R.; Corticelli, F.; Puglia, D.; Torre, L.; Terenzi, A.; Aluigi, A.
Abstract: This work investigates the preparation of wool keratin sponges by freeze-drying procedure starting form keratin aqueous solutions. The study highlights the correlations between process parameters (protein concentration and freezing rate) and the chemical-physical properties of the final sponges. In particular, as the keratin concentration increases from 1 to 20% wt, the mean pore size and the porosity decrease from 62 to 37 μm and from 94 to 50% respectively, while the chemical stability in physiological conditions increases, as well as the thermal stability and the elastic modulus. On the other hand, the increase of the freezing rate affects the design of sponges that appear as stacked leaflets structures with oriented pores. Moreover, in order to confer to keratin sponges antioxidant properties, polydopamine (PDA) nanoparticles were used as fillers. To this end, PDA nanoparticles of about 130 nm were successfully dispersed in the sponges, bestowing time-dependent anti-oxidant properties on the scaffolds, with no significant modification of sponges morphological structure as well as reduction of the thermal stability and mechanical behaviour. Graphical abstract: Highlights: Porous keratin sponges were prepared through freeze-drying process starting from aqueous solutions of the protein and in the complete absence of organic solvents The 3D-scaffolds properties can be controlled by a fine-tuning of the keratin concentration and freezing temperature The pore size and porosity decreases with increasing the keratin concentration Elsatic modulus as well as chemical and thermal stability increases with increasing the keratin concentration Solutions at higher keratin concentration generated sponges with lower pore size and porosity, but higher elastic modulus and higher chemical and thermal stability Polydopamine nanoparticles/keratin composite sponges displayed a time-dependent antioxidant activity The tunable keratin based sponges show promising perspectives in tissue-engineering and regenerative medicine.